Improving agriculture’s contribution to nutrition in Malawi: A conceptual introduction - Harris, Jody; Meerman, Janice; Aberman, Noora-Lisa (International Food Policy Research Institute, 2018)
With Malawian diets heavily dominated by staple foods—maize first and foremost, but also rice and cassava in some areas—food security in Malawi is often equated with having access to enough maize. What is missing in this traditional measure of food security in Malawi is the importance of the quality, in addition to the quantity, of dietary intake. This household-level scenario is reflected in, and exacerbated by, national development priorities; food security is a top-line agenda item for agriculture in Malawi, whereas nutrition is still considered primarily a health issue. To guide analysis and action in this complex environment, we present a conceptual framework to illuminate the multiple and complex linkages from agriculture to food security and nutrition. This framework reveals a number of ways in which the agriculture sector can help strengthen diet quality. These include: (1) promoting production of nutrient-dense foods via subsidies and other incentives; (2) promoting food processing, marketing, and consumption in ways that conserve nutrients, create demand, and decrease prices; and (3) supporting women farmers through, for example, targeted efforts to increase their productivity and bargaining power.